Female Entrepreneurship in Leading Digitalization as a Marketing Strategy for Prosperous MSMEs and Women's Empowerment: A Case Study of Latifa Indonesia - Rosepti, Popi; Niasari, Catur (Muslim Business and Economics Review, 2022)
Female entrepreneurship involves a movement where women can empower oneself and share their values with others. This study explores a business initiative led these principles: Latifa Indonesia, a maternal wellbeing therapy business founded by a female entrepreneur named Verawati. It describes the digital marketing strategy implemented by the company and analyzes several its impacts. The research employs a qualitative case study as well as semi-structured interviews, observation, and textual documentation to collect the data required. Thematic analysis, triangulation, and member checking are used while analyzing the obtained data. The finding of this study reveals that the digital marketing strategy used by Latifa Indonesia in establishing its business is implemented through the utilization of some digital platforms such as website, Facebook, and Instagram, but that transactions occur through WhatsApp, which is considered a more user-friendly application. The use of digital platforms positively impacted the company’s development, leading to increasing numbers of both new therapists and customers, improving the company’s accessibility, growing business income, and forming partnerships with other companies. Latifa’s business data from 2021 showed that both customers and income are increasing approximately 20 percent each year since the commencement of the business’ digital marketing strategy in 2017.